Uji Suka Butter Cake Gluten Free Berbahan Dasar Tepung Kedelai dan Tepung Mocaf - Indrayanti, Sri; Sopiyanti, Wina; Dwi Astuti, Ratih (CV. Creative Tugu Pena, 2024)
Butter cake comes from a type of pound cake that is traditionally made with the same ingredients to produce a type of cake that is soft, but easy to form. Butter cake is made from basic ingredients such as butter, flour, eggs, and sugar. Toasted soy flour can be used to add flavor and nutrition to cakes, breads, biscuits and other baked products. Mocaf flour is a flour product from cassava (Manihot esculenta) transformed through fermentation. In the approach taken in this study is experimental research and conducted by the method of research mix method. This study conducted a liking test to the panelists by using hedonic test to produce the best formulation. Based on the results of data collection from respondents showed that gluten free Butter cake products can be accepted by the public. In the sense indicator there are 3.47% of respondents agreed. In the aroma indicator, there are 3.5% of respondents stated that they strongly agree. In the texture indicator, there are 3.67% of respondents who agree very much. In the color indicator there are 3.43% of respondents agreed. In the display indicator there are 3.5% of respondents agreed. Gluten free Butter cake produced in this study can be a food choice for people who avoid gluten content for several personal reasons such as diet, autism, obesity, and others Keywords: Butter Cake, Gluten Free, Soybean Flour, Mocaf Flour